2008
DOI: 10.7589/0090-3558-44.4.791
|View full text |Cite
|
Sign up to set email alerts
|

Serologic Survey for Selected Viral Pathogens in Free-Ranging Endangered European Mink (Mustela Lutreola) and Other Mustelids From South-Western France

Abstract: ABSTRACT:To investigate the possible role of selected pathogens in the decline of endangered European mink (Mustela lutreola) populations and the potential for these pathogens to affect mink survival, a serologic survey was conducted using serum samples collected from March 1996 to March 2003 in eight departments of south-western France. In total, 481 free-ranging individuals of five mustelid species (including the European mink) were tested. Sympatric mustelids can serve as sentinels to determine the presence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 32 publications
1
31
0
Order By: Relevance
“…Nevertheless, the importance of CDV in urban and rural populations cannot be underscored, and it must be highlighted that CD has been classified as class 3 EID (i.e., a recognized infectious agent, affecting an emerging, new or increasing range of hosts, within a known geographical location) within the continental USA and Africa, since CDV endangers a wide host of carnivores, might be related to the extinction of the African wild dog and populations of black-footed ferrets, and threatens the survival of the Ethiopian wolf (DASZAK; CUNNINGHAM; HYATT, 2000). In Europe, CDV might be threatening the existence of the European mink, Mustela lutreola (PHILIPPA et al, 2008), and the Iberian lynx, Lynx pardinus (MELI et al, 2010).…”
Section: Source: Elaboration Of the Authorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, the importance of CDV in urban and rural populations cannot be underscored, and it must be highlighted that CD has been classified as class 3 EID (i.e., a recognized infectious agent, affecting an emerging, new or increasing range of hosts, within a known geographical location) within the continental USA and Africa, since CDV endangers a wide host of carnivores, might be related to the extinction of the African wild dog and populations of black-footed ferrets, and threatens the survival of the Ethiopian wolf (DASZAK; CUNNINGHAM; HYATT, 2000). In Europe, CDV might be threatening the existence of the European mink, Mustela lutreola (PHILIPPA et al, 2008), and the Iberian lynx, Lynx pardinus (MELI et al, 2010).…”
Section: Source: Elaboration Of the Authorsmentioning
confidence: 99%
“…In Europe, martens (Martes spp.) are considered as possible intermediate wildlife reservoirs of CDV (MYERS et al, 1997;PHILIPPA et al, 2008), and were attributed as sources of infection that resulted in the death of 19 large felids in Switzerland (MYERS et al, 1997). These animals live in close proximity with humans and are likely to become contaminated by CDV-infected dogs (PHILIPPA et al, 2008).…”
Section: Source: Elaboration Of the Authorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Identification of the role of infectious disease is an important concern for conservation strategies, especially because animals with low genetic diversity could be more vulnerable to infectious disease (O'Brien and Evermann, 1988). Recent studies of the western population of European mink revealed the prevalence of Aleutian disease virus and canine distemper virus, whereas exposure to other viral pathogens appeared to be low (Fournier-Chambrillon et al, 2004a;Philippa et al, 2008). Another potential disease is leptospirosis, a worldwide zoonotic disease caused by a pathogenic spirochete, Leptospira interrogans sensu lato (L. interrogans sl), which affects a wide range of vertebrates, including humans.…”
Section: Introductionmentioning
confidence: 99%
“…First, we investigated the prevalence of antibodies to L. interrogans sl in several freeranging small carnivores and in farmed American mink to measure exposure to this pathogen; second, we determined the prevalence of renal carriage of spirochetes in some species in order to better evaluate their potential epidemiologic role. (Fournier-Chambrillon et al, 2004a;Philippa et al, 2008). Individual animals were sometimes caught several times.…”
Section: Introductionmentioning
confidence: 99%